CONSTITUTIONAL FOUNDATIONS OF THE FUNCTIONING OF LOCAL SELF-GOVERNMENT - Melnichuk, Aleksandr; Melnichuk, Yulyia; Bocharov, Aleksandr; Stepanova, Diana; Kurbanov, Salman (Revista Inclusiones, 2021)
The article deals with the constitutional and legal foundations of the activities of local selfgovernment. Today, municipal power is one of the foundations of the development of modern society and statehood, so it is considered a key constitutional and legal structure. Problems and main directions of the development of the modern system of local self-government, theoretical concepts, features of legal regulation, as well as issues of the implementation of the municipal paradigm in practice, today are among the main objects of scientific understanding. In relation to them, diverse points of view and dilemmas not only in the Russian legal space but also foreign legal thought exist. The purpose of the present work is the analysis of constitutional and legal regulation of powers and competences of local self-government bodies and the assessment of the necessity of its revision and improvement based on the received conclusions.